José Luis León Manríquez (coord.), Historia mínima de Corea, México, El Colegio de México, 2009, 262 pp. - Pérez Gavilán, Graciela (Estudios de Asia y África, 2011)
José Luis León Manríquez (coord.), Historia mínima de Corea, México, El Colegio de México, 2009, 262 pp.